A meta-analysis of nursing students' knowledge and attitudes about end-of-life care. (December 2022) - Wang, Wei; Wu, Chenxi; Bai, Dingxi; Chen, Huan; Cai, Mingjin; Gao, Jing; Hou, Chaoming
Abstract: Objectives: To synthesize nursing students' knowledge and attitudes about end-of-life care and to identify strategic directions for optimizing end-of-life care education. Design: A meta-analysis of observational studies. Data sources: PubMed, Web of Science, EMBASE, CINAHL, PsycINFO, MEDLINE, CNKI, and WANFANG 8 electronic databases in English and Chinese were systematically searched from inception until 10 April 2022. Review methods: Two reviewers independently screened literature and extracted data using structured tables. The Agency for Healthcare Research and Quality (AHRQ) was used to appraise the methodological quality of included studies. The study outcomes were synthesized using a meta-analysis. Results: 26 cross-sectional studies of medium or high quality from 13 countries met the eligibility criteria, involving 9749 nursing students. In our review, nursing students demonstrated insufficient knowledge about end-of-life care, with a pooled mean score of 7.50 (95 % CI : 6.55–8.45); of these, knowledge about philosophy and principles, psychosocial and spiritual care, and pain and symptom management were all deficient, with pooled mean scores of 1.49 (95 % CI : 0.78–2.21), 1.00 (95 % CI : 0.35–1.65), and 3.44 (95 % CI : 2.25–4.63), respectively. Conversely, nursing students showed positive attitudes toward end-of-life care, with a pooled mean score of 102.97 (95 % CI : 99.43–106.51). The subgroup analysis revealed that male nursing students had lower pooled mean scores for end-of-life care knowledge and attitudes. Conclusion: There is a mismatch between nursing students' knowledge and attitudes about end-of-life care, they have a positive attitude but lack the necessary knowledge. Male nursing students seem to have a greater deficit of knowledge and a relatively conservative attitude toward end-of-life care. These findings may provide a significant reference for nursing educators to adjust educational strategies promptly. Highlights: This is the first meta-analysis of nursing students' knowledge and attitudes about end-of-life care. Nursing students have positive attitudes but lack the knowledge required for end-of-life care. Male nursing students have a greater knowledge deficit and a relatively conservative attitude toward end-of-life care. End-of-life education and teaching require a more coordinated educational strategy from nursing educators.